Singapore resale houses mobile application - Ng, Catherine Chew Ling (Nanyang Technological University, 2023)
Over the years, Singapore’s house prices have been rising and the demand to own a house remains high while there is only limited availability of houses. Many people struggle to buy houses, particularly new houses or Build to Order (BTO) flats due to the high property prices or long waiting times. As a result, many have turned to purchase resale houses because of the various benefits such as location, affordability, and space. This project aims to develop a mobile application to simplify the resale housing market in Singapore for property owners and potential buyers. The application provides a convenient solution to the complicated process of purchasing and selling resale houses in Singapore. This report describes the design, development, and implementation of a mobile application targeted at the Singapore resale housing market.